MELIHAT KEMUNGKINAN MODUS GEREJA SEBAGAI DASAR BAGI PENYUSUNAN MUSIK UNTUK HYMN - Daniel Sema (Tonika: Jurnal Penelitian dan Pengkajian Seni, 2018)
The standard major and minor scale have been used to compose millions of congregational song. After years of listening to music based on the same old scales, there is a way to break away from convention but still keep the music interested and more fresh. A great way to start exploring interesting and new sounding melodies and harmonies is to use modes (church modes). Modes are scales that use the same pitches of the standard major scale but in new and different ways. Because of one or two discrepancies from the typical major or minor scale, a mode can sound fresh, intriguing, and grab your listener's attention as something new.